On multipliers of hyper MV-algebras - Yang, Yongwei; Yangyang He (IJRDO -JOURNAL OF MATHEMATICS, 2019)
In the paper, we introduce the notion of multipliers of a hyper MV-algebra in the paper and investigate some properties of hyper MV-algebras in terms of multipliers. In addition, a set of equivalent conditions are established for two multipliers of a hyper MV-algebra to be equal in the sense of mappings. Further, some propositions of multipliers related with Fixd(M) are given